Electrochemical Sensor Based on Multi-Walled Carbon Nanotubes/ Gold Nanoparticles Composite for Determination of Melamine - Qu*, Jianying; Du, Xueping; Kang, Shiping; Lou, Tongfang (Asian Journal of Chemistry, 2013)
A new electrochemical sensor was prepared based on multi-walled carbon nanotubes/gold nanoparticles and Nafion composite film immobilized on glassy carbon electrode, which showed an excellent electrocatalytic activity for oxidation of melamine. Under optimal conditions, the oxidation peak current was found to be linearly related to melamine concentration over the range of 3.9 × 10-6-4.0 × 10-3 mol/L with a detection limit of 1.9 × 10-6 mol/L and the recovery ratio was 94.6-101 %. This method for determination of melamine exhibited good stability, reproducibility and with easy preparation, which showed potential applications for practice.